1993
DOI: 10.1136/bjo.77.12.778
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology of type II mesangiocapillary glomerulonephritis with associated fundus abnormalities.

Abstract: The retinal electrophysiology is reported in four patients with type II mesangiocapillary glomerulonephritis and partial lipodystrophy with associated fundus abnormalities and no visual symptoms. The histological hallmark of the condition is that of widespread electron dense deposits in the renal glomerulus and in the choriocapillaris and Bruch's membrane of the eye. Three of the four patients had the typical fundal appearance of multiple, yellow, drusen-like lesions at the posterior pole of the eye with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
1
13
0
4
Order By: Relevance
“…Their distribution is variable and as in AMD in the early stages, is not associated with ocular morbidity (Colville et al, 2003;Duvall-Young et al, 1989). With time retinal dysfunction may develop, detectable even when the patient is asymptomatic (Colville et al, 2003;D'Souza Y et al, 2009;O'Brien et al, 1993). Further progression can be associated with choroidal neovascularisation and serous macular detachment, although how frequently this occurs and whether it is complicated by the necessary pharmacotherapy is not known (Colville et al, 2003).…”
Section: Type II Membranoproliferative Glomerulonephritis Dense Depomentioning
confidence: 99%
“…Their distribution is variable and as in AMD in the early stages, is not associated with ocular morbidity (Colville et al, 2003;Duvall-Young et al, 1989). With time retinal dysfunction may develop, detectable even when the patient is asymptomatic (Colville et al, 2003;D'Souza Y et al, 2009;O'Brien et al, 1993). Further progression can be associated with choroidal neovascularisation and serous macular detachment, although how frequently this occurs and whether it is complicated by the necessary pharmacotherapy is not known (Colville et al, 2003).…”
Section: Type II Membranoproliferative Glomerulonephritis Dense Depomentioning
confidence: 99%
“…These are indistinguishable in composition and appearance from those in AMD (23,(31)(32)(33). Furthermore, one patient diagnosed with MPGNII harbors a mutation in the factor H gene (HF1), a major inhibitor of the alternative complement pathway (P. Zipfel, personal communication).…”
mentioning
confidence: 99%
“…42.67). 291,292 Histopathologic studies of the Bruch's membrane deposits found in MPGN II demonstrate that they are morphologically 293 and compositionally 294 similar to the drusen found in AMD. Mild functional abnormalities roughly correlate with more advanced age but patients with the red fenestrations have 20/20 visual acuity.…”
Section: Fenestrated Sheen Macular Dystrophy (Fsmd)mentioning
confidence: 95%